Opioid Use in Cancer Pain Management in Indonesia: a Call For Attention - Rianto Setiabudy; Cosphiadi Irawan; Aru W Sudoyo (Acta Medica Indonesiana)
Severe pain is a major problem for cancer patients, and pain management often requires the use of opioids. Indonesia is one of the countries where the use of opioids for cancer patients is extremely low, and this calls for attention, as many cancer patients in the country undergo unnecessary suffering as the consequence of this opioid underuse. The inability to assess pain correctly, failure to determine the correct dose, fear of addiction, overly tight regulation, all contribute to the failure to implement rational use of opioids for cancer patients. Breakthrough pain, a problem which requires special attention not only because it is commonly found but also requires proper knowledge to handle them. These hurdles are discussed in the present review, in order to bring a better understanding about the correct use of opioids in severe cancer pain. Some examples where opiods are used inappropriately in cancer pain management are also discussed.